'I'm not just a guinea pig': Academic and community perceptions of participatory autism research. (January 2021) - den Houting, Jacquiline; Higgins, Julianne; Isaacs, Kathy; Mahony, Joanne; Pellicano, Elizabeth
Despite calls for increased community engagement in autism research, the published evidence base suggests that participatory autism research remains rare. This study examined the extent and nature of community engagement in Australian research projects commissioned by the Autism CRC. Data were gathered using an online survey, comprising quantitative scale items and qualitative free-text responses, which was completed by 64 academic partners and 15 community partners. Quantitative findings indicated that autism research stakeholders in Australia are largely supportive of community engagement in research and have had positive experiences of participatory research. These findings were not wholly corroborated by the qualitative findings, however, which suggested that participants lacked understanding of participatory research, and held attitudes that may hinder the conduct of successful participatory research. Systemic issues within research settings were also perceived to impede community engagement in research. Both academic and community partners would benefit from better understanding of participatory research approaches, paired with practical and epistemological shifts at the systemic level, to ensure that future community engagement in autism research is respectful, equitable and beneficial to all stakeholders. Lay abstract: Participatory research means working together ( engaging ) with the community that is affected by research to make decisions about that research. Participatory research is common in some fields, but it is still rare in autism research. In this study, we wanted to find out how Australian autism researchers and community members feel about participatory research. We worked with an Autistic Advisory Group to design this study, understand the results and write this article. We asked 127 people, all working on research from the Cooperative Research Centre for Living with Autism, to complete an online survey about participatory research. The survey included some questions that were answered on rating scales, and some where participants wrote their own answers. Seventy-nine people (64 researchers and 15 community members) completed most or all of the survey. The rating scales showed that most participants (82%) supported moderate or extensive community engagement in research, and most participants (72%) thought there should be more community engagement in autism research. In general, the participants rated their experiences of participatory research positively. Using the participants' own written answers, we found four main ideas: (1) participatory research is important, but difficult; (2) many people do not fully understand what participatory research is; (3) academics and community members do not work together as = and (4) research systems are not designed for participatory research. Our results suggest that autism researchers and community members want to do more participatory research, but they might need training, support and funding to do participatory research well.